Endothelial Progenitors: A Consensus Statement on Nomenclature - Medina,RJ; Barber,CL; Sabatier,F; Dignat-George,F; Melero-Martin,JM; Khosrotehrani,K; Ohneda,O; Randi,AM; Chan,JKY; Yamaguchi,T; Van,Hinsbergh VWM; Yoder,MC; et al. (Stem Cells Translational Medicine, 2017)
Endothelial progenitor cell (EPC) nomenclature remains ambiguous and there is a general lack of concordance in the stem cell fieldwith many distinct cell subtypes continually grouped under the term “EPC.” It would be highly advantageous to agree on standards toconfirm an endothelial progenitor phenotype and this should include detailed immunophenotyping, potency assays, and clear separationfrom hematopoietic angiogenic cells which are not endothelial progenitors. In this review, we seek to discourage the indiscriminateuse of “EPCs,” and instead propose precise terminology based on defining cellular phenotype and function. Endothelial colonyforming cells and myeloid angiogenic cells are examples of two distinct and well-defined cell types that have been considered EPCsbecause they both promote vascular repair, albeit by completely different mechanisms of action. It is acknowledged that scientificnomenclature should be a dynamic process driven by technological and conceptual advances; ergo the ongoing “EPC” nomenclatureought not to be permanent and should become more precise in the light of strong scientific evidence. This is especially important asthese cells become recognized for their role in vascular repair in health and disease and, in some cases, progress toward use in celltherapy.